2019
DOI: 10.1016/j.stemcr.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-Derived Retinal Pigment Epithelium: A Model System for Prioritizing and Functionally Characterizing Causal Variants at AMD Risk Loci

Abstract: Summary We evaluate whether human induced pluripotent stem cell-derived retinal pigment epithelium (iPSC-RPE) cells can be used to prioritize and functionally characterize causal variants at age-related macular degeneration (AMD) risk loci. We generated iPSC-RPE from six subjects and show that they have morphological and molecular characteristics similar to those of native RPE. We generated RNA-seq, ATAC-seq, and H3K27ac ChIP-seq data and observed high similarity in gene expression and enriched tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Our group 21 and others have successfully applied the iPSC approach to generate disease models for AMD 42 . These have helped to identify and/or validate the disease risk alleles 43 generated by genome‐wide association studies 42 and to highlight key cellular phenotypes in AMD‐RPE related to reduced defense against oxidative damage, 44 mitochondrial DNA damage and disintegration, 45 higher expression of complement and inflammatory markers, 46 dysregulated autophagy, 16,21,47 and activation of inflammasome signaling 48 . Focusing on a key high‐risk polymorphism (Y402H) in the complement factor gene, we have used the iPSC‐derived RPE cells to identify which step(s) of autophagy‐lysosome pathway is (are) affected in AMD patients, how it is controlled and test whether it can be reversed.…”
Section: Discussionmentioning
confidence: 99%
“…Our group 21 and others have successfully applied the iPSC approach to generate disease models for AMD 42 . These have helped to identify and/or validate the disease risk alleles 43 generated by genome‐wide association studies 42 and to highlight key cellular phenotypes in AMD‐RPE related to reduced defense against oxidative damage, 44 mitochondrial DNA damage and disintegration, 45 higher expression of complement and inflammatory markers, 46 dysregulated autophagy, 16,21,47 and activation of inflammasome signaling 48 . Focusing on a key high‐risk polymorphism (Y402H) in the complement factor gene, we have used the iPSC‐derived RPE cells to identify which step(s) of autophagy‐lysosome pathway is (are) affected in AMD patients, how it is controlled and test whether it can be reversed.…”
Section: Discussionmentioning
confidence: 99%
“…iPSC-RPE cells share a similar background to human RPE cells, and thus can be used as a predictive model to characterize genetic risk variants. In their study, Smith et al [ 23 ] showed that the patient-derived iPSC RPE gene expression profile is highly similar to that of their native RPE cells. Golestaneh et al [ 24 ] generated iPSC RPE models from healthy and vAMD donors that exhibit a specific disease phenotype.…”
Section: In Vitro Models Of Vamdmentioning
confidence: 99%
“…When left longer in culture to mature, bestrophin 1 (BEST1) and RPE-specific protein of 65 kDa (RPE65) were also strongly expressed ( Maruotti et al, 2015 ). Using a slightly adapted protocol, Smith et al (2019) differentiated six more hiPSC lines into hiPSC-RPE monolayers, all six also expressed the key RPE markers ZO-1, BEST-1, and MITF. Another study revealed by RNA sequencing data that hiPSC-RPE grouped with fetal RPE samples, indicating that their gene expression was highly correlated and similar ( Smith et al, 2019 ).…”
Section: Human-derived Retinal Modelsmentioning
confidence: 99%